2017
DOI: 10.1186/s12864-017-4377-z
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification, characterization, and evolutionary analysis of flowering genes in radish (Raphanus sativus L.)

Abstract: BackgroundRadish (Raphanus sativus L.) belongs to the family Brassicaceae, and is an economically important root crop grown worldwide. Flowering is necessary for plant propagation, but it is also an important agronomic trait influencing R. sativus fleshy taproot yield and quality in the case of an imbalance between vegetative and reproductive growth. There is currently a lack of detailed information regarding the pathways regulating the flowering genes or their evolution in R. sativus. The release of the R. sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 57 publications
1
24
0
1
Order By: Relevance
“…Previous studies have revealed that the circadian clock is tissue-specific (Thain et al , 2002; Endo et al , 2014; Bordage et al , 2016). Differential expression of clock genes has been reported in several tissues including seeds, roots, leaves, stems and flowers at several developmental stages in different plant species such as bamboo (Dutta et al , 2018), radish (Wang et al , 2017) or daisy (Fu et al , 2014). The present study has covered several clock genes, including GI and PRRs paralogs, in petunia leaves and petals and our results are consistent with the existence of organ-specific biological clocks in plants.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have revealed that the circadian clock is tissue-specific (Thain et al , 2002; Endo et al , 2014; Bordage et al , 2016). Differential expression of clock genes has been reported in several tissues including seeds, roots, leaves, stems and flowers at several developmental stages in different plant species such as bamboo (Dutta et al , 2018), radish (Wang et al , 2017) or daisy (Fu et al , 2014). The present study has covered several clock genes, including GI and PRRs paralogs, in petunia leaves and petals and our results are consistent with the existence of organ-specific biological clocks in plants.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, a total of 1064, 510, and 524 flowering-time genes were identified from B. napus , B. rapa , and B. oleracea , respectively. Compared to other crops or plants, it appears that Brassica crops possess more flowering-time genes [ 22 , 24 , 40 ], due to whole genome triplication (WGT) and a genome merging event during their evolution [ 32 ]. However, no orthologs for some flowering-time genes were found in the Brassica species we studied, suggesting gene loss or genome contraction may have occurred in Brassica after WGT [ 32 , 34 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the control of flowering time in crops is not only important for improving crop yield, but also provides a theoretical basis for cultivating crops using diverse farming practices. To date, flowering-time genes have been extensively identified and studied in several crops, including cotton ( Gossypium raimondii ), radish ( Raphanus sativus ), wheat ( Triticum aestivum ), and barley ( Hordeum vulgare ) [ 21 , 22 , 23 , 24 , 25 ]. However, this is not the case for crops from the genus Brassica .…”
Section: Introductionmentioning
confidence: 99%
“…Genes involved in flowering pathways in B. rapa have been identified (Wang et al, 2017), and 89 genes mainly involved in vernalization and autonomous pathways were selected in this study (Table S4). In our RNA-seq data, 29 out of 89 genes showed differential expression in vernalized samples compared with nonvernalized samples for at least one cold treatment condition ( Fig.…”
Section: Transcriptional Changes In Flowering Pathway Genes Followingmentioning
confidence: 99%